Dynamics of Carotid Intima-Media Thickness, Parameters of Arterial Stiffness and Ambulatory Blood Pressure Monitoring during Therapy with Inhibitor of Tumor Necrosis Factor-Alpha in Patients with Early Psoriatic Arthritis - E. I. Markelova; D. S. Novikova; T. V. Korotaeva; E. Yu. Loginova (Столичная издательская компания, 2018)
Background. Patients with psoriatic arthritis (PsA) have increased risk of cardiovascular diseases (CVD). Anti-tumor necrosis factor (TNF) therapy is an effective in PsA but its cardiovascular effects are poorly understood.Aim. To study the changes in carotid intima-media thickness (c-IMT), parameters of arterial stiffness (AS), ambulatory blood pressure monitoring (AMBP) in early PsA (EPsA) patients during the anti-TNF therapy with adalimumab (ADA).Material and methods. Patients with EPsA (n=16; 11 females, 5 males; median age 45.5 years, EPsA duration - 7.7  months) were included into the study. All patients were treated with ADA 40 mg every other week up to 3 months. At baseline and after 3 months of therapy all patients were assessed  for conventional cardiovascular risk factors, DAS (Disease Activity Score) and  HAQ (Health Assessment Questionnaire) indices, C-reactive protein (CRP), c-IMT, ABPM. At baseline the  4 patients had  arterial hypertension, and  all patients received effective antihypertensive therapy. All patients were assessed for AS parameters: carotid-femoral pulse wave velocity (PWVcf) and index of wave reflection (rigidity index; RI, %). c-IMT was measured using a high-resolution B-mode ultrasound machine. The results are presented in the form of a median - Me (25; 75 percentiles).Results. By the end of the 3rd month of therapy, a decrease in the activity of early PsA was observed as compared to baseline values: DAS decreased from 4.6 (2.9; 1.9) to 1.6 (1.3; 1.9), p=0,001; HAQ from 0.93 (0.81; 1.31) to 0.25 (0; 0.56), p=0,001; CRP from 27.2 (9.7; 33.7) to 1.8 (0.8; 3.1) mg/l, p=0.001. EPsA remission (DAS<1.6) was achieved in 94% of patients. By the end of therapy c-IMT decreased from 0.8 (0.74; 0.85) to 0.73 (0.58; 0.77) mm, p=0,01; as well as AS parameters: PWVcf from 9.9 (7.7; 17.7) to 9.2 (7.4; 10.6) m/s, p<0.05; RI from 69.5 (58; 74) to 49.5 (44; 64)%, p<0.05. AMBPs parameters didn't change significantly. We found significant (p=0.03) decrease in the frequency of the increase in 24-hour diastolic blood pressure.Conclusions. Anti-TNF treatment with ADA improves arterial wall state by decreasing inflammation. These data confirm the idea that inflammation involves in acceleration of atherosclerosis in EPsA patients.